PLC-SCADA Automation of Inlet Wastewater Treatment Processes: Design, Implementation, and Evaluation - Kadhim Hassan Kaittan; Samir Jasim Mohammed (Journal Europeen des Systemes Automatises, 2024)
The intelligent automation of inlet wastewater treatment plants necessitates the deployment of integrated control systems such as programmable logic controllers (PLCs). These systems manage the continuous operation of pumps, valves, and biochemical processes through precisely designed electrical algorithms, achieving a high-level processing system. This study presents an innovative approach to the design and evaluation of ladder block algorithms for optimizing processors rapidly by leveraging PLCs to organize data analysis, display, and supervisory control and data acquisition (SCADA). The proposed methodology involves establishing a connection between the SCADA system and the Siemens PLC-S7-300 controller to enable efficient and rapid calculations. The results demonstrate that the ideal electrical algorithm derived from the biochemical system's behaviour, implemented through the PLC S7-300 Siemens, effectively treats incoming wastewater. This system ensures precise monitoring and control, promptly recording and notifying on-site personnel of any unexpected events, such as biochemical defects or electrical malfunctions, and adapting to these issues using the designed algorithm. The system is developed using Totally Integrated Automation (TIA) portal software, underscoring its robustness and reliability in managing wastewater treatment processes.